Survey on the current diseases status of local versus improved cassava varieties and their management strategies in Cameroon - Tindo, M.; Njukwe, E.; Mbairanodji, A.; Tenkouano, A. (2016)
We conducted two main surveys in 29 sites within the five antennae of the Cameroon National Program for Roots and Tubers Development (PNDRT), to assess potential changes triggered by the introduction of improved varieties on cassavadisease status. Standard methods were used to evaluate diseases incidences and damages severities on both local and improved varieties. Symptoms of six diseases were observed in cassava fields including cassava mosaic disease (CMD), cassava anthracnose disease (CAD); cassava bacterial blight (CBB), cassava root rot (CRR), cassava brown leaf spot and cassava white leaf spot. The incidence and severity of these diseases varied considerably between antennae, sites and cassava varieties. Their severities were generally mild to moderate. In general, local varieties were significantly more attacked by CMD and CBB than improved ones while CAD infested equally both varieties. In conclusion, the introduction of improved cassava varieties has significantly reduced the incidence and severity of CMD and CBB effect on cassava development and consequently on yield. Despite this achievement, CAD and root rot remain a problem for cassava production in Cameroon Collaborative effort should therefore continue to develop, select and introduce resistant material against major diseases.